PENGARUH PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG PEMERIKSAAN ANTENATAL CARE (ANC) TERPADU DI KLINIK CITRA PALEMBANG - Untari Anggeni; Sri Emilda; Pita Purnama Sari; Nurbaity (Jurnal Kesehatan dan Pembangunan, 2026)
Antenatal Care (ANC) is an essential pregnancy examination to monitor maternal and fetal health. One of the common problems among pregnant women is inadequate knowledge and attitudes toward pregnancy and health services, which may lead to low ANC attendance. Therefore, intensive health education is needed to improve pregnant women’s knowledge and attitudes regarding the importance of routine antenatal examinations. This study aimed to determine the effect of health education on pregnant women’s knowledge and attitudes toward integrated ANC services at Citra Clinic, Palembang. This quantitative study employed a pre-experimental design using a one-group pretest–posttest approach. The population consisted of all pregnant women who attended integrated ANC services at Citra Clinic, Palembang, from August to December 2023. A total of 46 respondents were selected using purposive sampling. Data were collected using a questionnaire and analyzed through bivariate testing. Normality testing showed that knowledge data were not normally distributed; therefore, the Wilcoxon Signed Rank Test was used. Attitude data were normally distributed and analyzed using a paired t-test. The results revealed a significant improvement in pregnant women’s knowledge (Z = -3.970; p < 0.001) and attitudes (t = -3.402; p = 0.001) after receiving health education. In conclusion, health education significantly influences pregnant women’s knowledge and attitudes toward integrated ANC services. It is recommended that pregnant women actively participate in health education sessions to enhance their knowledge and develop more positive attitudes toward routine antenatal care.